Study on Material Innovation and Electrochemical Performance in Solid-State Battery Technology for Sustainable Energy Applications - Herlina Rahim; Rozlinda Dewi; Venny Yusiana; Rismen Sinambela (Science Journal Get Press, 2026)
Solid-state batteries (SSBs) have gained strong attention for their higher safety, greater energy density, and improved electrochemical stability compared to liquid-electrolyte lithium-ion batteries, although challenges remain in optimizing ionic conductivity, interfacial resistance, and cycling stability. This study investigates the synthesis, structural characteristics, and electrochemical performance of the argyrodite solid electrolyte Li₆PS₅Cl (LPSC), produced via high-energy mechanical milling and integrated into a prototype SSB using a Li-metal anode and NMC811 cathode. XRD analysis confirmed the formation of the cubic argyrodite phase, while SEM revealed a homogeneous particle morphology conducive to efficient ion transport. Electrochemical impedance spectroscopy (EIS) showed an ionic conductivity of 1.87 × 10⁻³ S/cm at 25°C, which increased to 3.41 × 10⁻³ S/cm after annealing at 550°C. Galvanostatic cycling at 0.1C demonstrated stable capacity retention of 92.5% after 50 cycles, indicating strong interfacial contact between the LPSC electrolyte and NMC811 cathode. Comparative evaluation with recent SSB literature shows that the optimized LPSC electrolyte achieves performance levels comparable to state-of-the-art sulfide-based electrolytes due to improved crystallinity and reduced grain-boundary resistance. These results highlight the potential of mechanically milled LPSC as a promising solid electrolyte for next-generation SSB applications.